Mild Neurological Phenotype Associated with Hypomorphic Variants in the Ataxia‐Telangiectasia Mutated Gene. Issue 1 (10th December 2022) - Caputi, Caterina; Federici, Giulia; Soddu, Silvia; Travaglini, Lorena; Piane, Maria; Bertini, Enrico; Zanni, Ginevra; Leuzzi, Vincenzo
ABSTRACT: Background: Ataxia‐telangiectasia (A‐T) is a progressive multisystemic neurodegenerative disease. The phenotypic spectrum includes conditions (variant A‐T) with mild, late‐onset, and atypical clinical presentations characterized by the prevalence of dyskinetic rather than ataxic features. Cases: We describe the clinical presentations of 3 siblings with early‐onset truncal ataxia without obvious neurological deterioration or biological markers of classic A‐T phenotype. We performed functional and genetic evaluation of 3 siblings with very mild neurological phenotype. Genetic evaluation with a next‐generation sequencing panel for genes causative of cerebellar ataxia detected 2 known ATM gene variants, missense c.9023G>A p.(Arg3008His), and leaky splicing c.1066‐6T>G variants. Functional studies showed mildly reduced ATM expression and residual kinase activity in the probands compared with healthy controls. Conclusions: These results suggest the importance of investigating ATM variants even in the presence of clinical and biological atypical cases to ensure specific therapeutic regimens and oncological surveillance in these patients.